2017
DOI: 10.1016/j.midw.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

“Am I too emotional for this job?” An exploration of student midwives' experiences of coping with traumatic events in the labour ward

Abstract: for midwifery educators, a focus on the psychological complexities in the midwifery role could assist in giving voice to and normalising the inevitable anxieties and difficulties inherent in the role. Further research could explore whether assisting students to have a psychological language with which to reflect upon this emotionally challenging work may promote safety, resilience and self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 36 publications
(36 reference statements)
0
55
0
4
Order By: Relevance
“…Perinatal care, in particular, is often considered a joyous time of life, but perinatal care providers may also be present during intrapartum emergencies, traumatic births, or maternal and fetal deaths. 3,4 Adverse events resulting in patient harm can have a significant impact on the lives of patients and their families 5,6 and also adversely affect the lives of perinatal care providers involved in these events whether or not the event was preventable. [7][8][9][10][11][12] The term second victim describes the phenomenon of trauma experienced by a health care provider who is involved in an adverse health care-related event .…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal care, in particular, is often considered a joyous time of life, but perinatal care providers may also be present during intrapartum emergencies, traumatic births, or maternal and fetal deaths. 3,4 Adverse events resulting in patient harm can have a significant impact on the lives of patients and their families 5,6 and also adversely affect the lives of perinatal care providers involved in these events whether or not the event was preventable. [7][8][9][10][11][12] The term second victim describes the phenomenon of trauma experienced by a health care provider who is involved in an adverse health care-related event .…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen per cent of practising midwives in the Netherlands reported to having been involved in a traumatic work-related event, resulting in post-traumatic stress for some of them (2.2% of practising midwives) 10 . Studies among midwifery students reported high levels of involvement in traumatic work-related events [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Since health of midwives and midwifery students directly affects the quality of maternal care, these stresses must be adequately moderated by instructors' support [10]. The focus of instructors on the psychological complexities of midwifery role can be effective in adjusting and normalizing the inevitable tensions and inherent problems of this profession [7]. It seems the best way forward would be education for clinical instructors in how better to support the clinical learning of future midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Learning and practice in health sciences including midwifery are intrinsically stressful [1][2][3][4]. Midwifery is an emotionally challenging profession, and midwifery education has its own specific challenges [5][6][7]. Stress is a pervasive problem in midwifery education which affects the theoretical and practical learning [2][3][4].…”
Section: Introductionmentioning
confidence: 99%